Ethanol Extract of Nigella sativa Attenuates Eosinophilic Inflammation and Epithelial Remodeling in an Ovalbumin-Induced Rat Model - Dewi, Rika Sari; Sandhiutami, Ni Made Dwi; Desmiaty, Yesi; Dwiantika, Ajeng Sunthi (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Allergic airway inflammation is commonly associated with eosinophilic infiltration and epithelial remodeling, which impair respiratory function and contribute to tissue damage. This study investigated the therapeutic potential of the ethanol extract of Nigella sativa in an ovalbumin-induced rat model of allergenic airway response. Ethanol extracts were tested in an ovalbumin-induced rat model using Sprague-Dawley rats (n=36), comparing normal, negative controls, 0.009 mg/g BW salbutamol (positive control), and three inhaled extract doses (12.25, 24.50, 49 g/kg BW). Comprehensive analysis included physiological parameters (oxygen saturation), inflammatory biomarkers (lung eosinophil count), and pulmonary histopathology (epithelial thickness). The highest dose (49 g/kg) matched salbutamol in improving oxygen saturation (86.75% vs. 88%, p=0.9917) and reducing epithelial thickness (81.50 µm vs. 81.75 µm, p=0.9999), while suppressing eosinophil infiltration (0.73 vs. 1.45 cells/field, p=0.3348). These results confirm Nigella sativa’s efficacy in attenuating airway inflammation via eosinophil-targeted mechanisms without structural epithelial alterations. The study validates traditional applications of Nigella sativa and proposes an evidence-based framework for integrating phytotherapy into respiratory medicine.